تكامل الأسواق المالية في مجموعة من دول شرق المتوسط ومجموعة من دول غرب المتوسط (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This paper aims to study the integration of financial markets in a group of Eastern Mediterranean countries (Syria, Jordan, Lebanon, Turkey) and a group of Western Mediterranean countries (Egypt, Tunisia, Morocco, France).The long term relationship between the returns of the monthly closing prices of financial markets indicators during the period of 2010-2017 was examined on AutoRegressive Distributed Lag (ARDL) model. The relationship in the short term was also studied based on Vectorial AutoRegressive (VAR) model, the impact of external and internal shocks on returns was discovered through impulse response function and variance decomposition. The results of ARDL model showed that the integration markets in the Western Mediterranean countries is stronger than the integration in Estern Mediterranean, while the Granger test shoewd that the relation is weak in the short term in both groups. The response function indicated that markets responed differently to external shoks, and on the variance decompostion we found that; in most markets the internal shoks are more able to explain fluctuations in returns of financial markets indicators. يهدف هذا البحث إلى دراسة تكامل الأسواق المالية في مجموعة من دول شرق المتوسط (سورية، الأردن، لبنان، تركيا) ومجموعة من دول غرب المتوسط (مصر، تونس، المغرب، فرنسا). لتحقيق هدف البحث قُدرت العلاقة على الأجل الطويل بين عوائد أسعار الإغلاق الشهرية لمؤشرات الأسواق المالية خلال الفترة (2010-2017م) بالاعتماد على نموذج الانحدار الذاتي لفترات الإبطاء الموزّعة (AutoRegressive Distributed Lag(ARDL)). كما دُرست العلاقة على الأجل القصير بالاعتماد على نموذج الانحدار الذاتي الشعاعي (Vectorial AutoRegressive(VAR))، وتم اكتشاف أثر الصدمات الخارجية والذاتية على العوائد من خلال دوال استجابة النبضة وتحليل التباين. أظهرت نتائج اختبار (ARDL) أنّ تكامل الأسواق المالية بين مجموعة دول غرب المتوسط أقوى ممّا هو عليه بين مجموعة دول شرق المتوسط، فيما أوضح اختبار ((Granger أن العلاقة ضعيفة على الأجل القصير في كلا المجموعتين. بيّنت دوال الاستجابة أن الأسواق المالية تستجيب بشكل متباين للصدمات الخارجية، وفيما يتعلق بتحليل التباين وجدنا أن الصدمات الذاتية في معظم الأسواق قادرة بشكلٍ أكبر على تفسير التذبذبات في عوائد مؤشراتها.